Proficiency pairing and engagement with language in L2 peer interaction. (April 2022) - Zabihi, Reza; Ghahramanzadeh, Behnoush
Abstract: This study investigated whether interlocutor proficiency affected engagement with language during a joint composition task completed by 54 learners in three types of pairs: low-low, low-high and high-high. The LREs were divided into cognitive conflict episodes (CCEs) and non-cognitive conflict episodes (non-CCEs) according to the extent to which learners deliberated over language features and challenged one another's contributions. Pairs' engagement was assessed in terms of the number, type (lexical or grammatical-based) and resolution (correct, incorrect, or unresolved) of CCEs jointly produced during collaborative dialogues. The results showed that high-high pairs produced and correctly resolved significantly more CCEs than either the low-low pairs or the low-high pairs, and that pairing low proficiency learners with high proficiency partners could weaken the pairs' engagement levels. However, interlocutor proficiency did not affect the types of language form pairs focused on. Individual learners' engagement was assessed in terms of learners' cognitive (initiating LREs; producing idea units), affective (instances of laughter and expression of enjoyment; self-reported emotions), and social (providing help; giving encouragement; showing responsiveness) states when completing the task. While high proficiency learners demonstrated higher cognitive and social engagement when they were paired with similar, highly proficient partners, lower proficiency learners reported greater affective engagement when working with other low proficiency partners.